The Role of Monetary Policy on Economic Growth: Evidence from Indonesia - Agustina, Clarissa Rahma; Daryono, Daryono (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The main determinant of a country’s economic condition is economic growth. The analysis used in this study is Ordinary Least Square (OLS) regression analysis and aims to determine how the influence of the money supply (JUB), inflation (INF), and interest rates (BIRATE) on Indonesia’s economic growth for the period 2002 to 2021. Inflation, the money supply, and interest rates are independent variables in this study, while economic growth is the dependent variable. The results showed that inflation had no effect on economic growth. The money supply variable has a positive effect on economic growth while the interest rate has a negative effect on economic growth.